Arthroscopic Repair of Double Radial Tears of the Lateral Meniscus - Leafblad, Nels D. (Arthrosc Tech, 2019)
Double radial tears of the lateral meniscus are rare injuries that typically occur in the setting of an acute anterior cruciate ligament rupture. Full-thickness radial tears of the meniscus body and root render the meniscus nonfunctional from a loss of hoop stress resistance. Repair of these tears can normalize contact pressures in the lateral compartment and delay arthritic changes. We describe our technique for repairing a lateral meniscus body radial tear and concomitant posterior root tear, via inside-out suture repair and transtibial suture repair, respectively. This investigation was performed at Mayo Clinic.